Development of an artificial intelligence-based multimodal diagnostic system for early detection of biliary atresia - Ya Ma; Yuancheng Yang; Yuxin Du; Luyang Jin; Baoyu Liang; Yuqi Zhang; Yedi Wang; Luyu Liu; Zijian Zhang; Zelong Jin; Zhimin Qiu; Mao Ye; et al. (BMC Medicine)
Abstract Background Early diagnosis of biliary atresia (BA) is crucial for improving patient outcomes, yet remains a significant global challenge. This challenge may be ameliorated through the application of artificial intelligence (AI). Despite the promise of AI in medical diagnostics, its application to multimodal BA data has not yet achieved substantial breakthroughs. This study aims to leverage diverse data sources and formats to develop an intelligent diagnostic system for BA. Methods We constructed the largest known multimodal BA dataset, comprising ultrasound images, clinical data, and laboratory results. Using this dataset, we developed a novel deep learning model and simplified it using easily obtainable data, eliminating the need for blood samples. The models were externally validated in a prospective study. We compared the performance of our model with human experts of varying expertise levels and evaluated the AI system’s potential to enhance its diagnostic accuracy. Results The retrospective study included 1579 participants. The multimodal model achieved an AUC of 0.9870 on the internal test set, outperforming human experts. The simplified model yielded an AUC of 0.9799. In the prospective study’s external test set of 171 cases, the multimodal model achieved an AUC of 0.9740, comparable to that of a radiologist with over 10 years of experience (AUC = 0.9766). For less experienced radiologists, the AI-assisted diagnostic AUC improved from 0.6667 to 0.9006. Conclusions This AI-based screening application effectively facilitates early diagnosis of BA and serves as a valuable reference for addressing common challenges in rare diseases. The model’s high accuracy and its ability to enhance the diagnostic performance of human experts underscore its potential for significant clinical impact.